2019
DOI: 10.1038/s41598-019-50918-2
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility, viral dynamics and persistence of South American Zika virus in New World monkey species

Abstract: South American Zika virus (ZIKV) recently emerged as a novel human pathogen, linked with neurological disorders. However, comparative ZIKV infectivity studies in New World primates are lacking. Two members of the Callitrichidae family, common marmosets (Callithrix jacchus) and red-bellied tamarins (Saguinus labiatus), were highly susceptible to sub-cutaneous challenge with the Puerto Rico-origin ZIKVPRVABC59 strain. Both exhibited rapid, high, acute viraemia with early neuroinvasion (3 days) in peripheral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 51 publications
2
38
1
Order By: Relevance
“…Investigation of ZIKV deposits in tissues revealed that primates infected subcutaneously with ZIKV presented detectable viral RNA over 60 days in the central and peripheral neuronal tissues, and other deposits have been already described in the for Rhesus macaque and Redbellied tamarin infected models (12).…”
Section: Discussionmentioning
confidence: 63%
“…Investigation of ZIKV deposits in tissues revealed that primates infected subcutaneously with ZIKV presented detectable viral RNA over 60 days in the central and peripheral neuronal tissues, and other deposits have been already described in the for Rhesus macaque and Redbellied tamarin infected models (12).…”
Section: Discussionmentioning
confidence: 63%
“…Due to similarities in natural history between YFV and ZIKV, concerns have grown about the possibility of ZIKV establishing a sylvatic cycle in Brazil, which would prevent its eradication, as happened with YFV [4]. Although ZIKV has never been isolated from any other vertebrate besides humans in the Americas, and sylvatic NHP-biting mosquitoes have never been detected to be naturally infected with ZIKV, the findings of RNA fragments compatible with ZIKV and antibodies against this virus in synanthropic marmosets and capuchin monkeys captured in peri urban areas in Brazil, and the demonstration that marmosets can experimentally sustain viremia [23][24][25] have led to the hypothesis that NHPs would play a role in sustaining the urban transmission cycle or in establishing an sylvatic transmission cycle in the Americas.…”
Section: Introductionmentioning
confidence: 99%
“…International initiatives were established to better understand virus pathogenesis and develop strategies to combat future outbreaks. Studies conducted in different NHP species have elucidated pathogenesis whereby ZIKV is no longer regarded simply as a self-limiting acute infection but persisting viral signals have been detected in multiple anatomical sites many weeks after the initial infection has cleared from the blood [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV has a broad host range capable of productively infecting a spectrum of higher mammals including humans and both Old and New World monkey species 16,17 . Antibody responses to major viral proteins (e.g., NS-1 and envelope antigens), particularly a broadly neutralising antibody response, are associated with recovery from ZIKV infection that appears to confer protective immunity against re-infection, with a lack of new infections in exposed, immune populations as confirmed by epidemiological studies 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation